Crossfire trail - L'Amour, Louis (Greenwich, Conn. Fawcett Publications, 1974)
Rafe Caradec$1 (Bgambler, wanderer, soldier of fortune$1 (Bwas as hard a man as the battlefields and waterfronts of Latin America could fashion, but he was as good as his word. As Charles Rodney lay dying in a dank ship$1 (Bs fo$1 (Bc$1 (Bsle, Rafe swore to make sure that Rodney$1 (Bs Wyoming ranch went to his daughter, Ann. In Painted Rock, Wyoming, Caradec found land for a man to love, miles of rolling grasslands and towering mountains. He also found that one of the most ruthless men in the territory had set his sights on both Rodney$1 (Bs ranch and his daughter. But Rafe Caradec had given his word, and once he$1 (Bd looked deep into Ann Rodney$1 (Bs eyes, nothing short of death would stop him from keeping the promise he$1 (Bd made.s
89718
Keywords: Gamgs